Mickalene Thomas - portrait of an unlikely space - Thomas, Mickalene 1971- (Yale University Art Gallery, 2023)
Mickalene Thomas (b. 1971) has gained an international reputation for her dazzling portraits of Black women, as well as her large-scale installations that physically enfold viewers into lushly decorated, 1970s-inspired domestic interiors. This volume offers a window into Thomas’s unique, multifaceted approach and introduces a new living room–style installation by the artist, in which she creates, for the first time, a homelike environment reminiscent of the pre-abolition era. In addition to period-specific textile patterns and other decorative elements, her installation incorporates a selection of small-scale, early American portraits of Black women, men, and children—from miniatures and daguerreotypes to silhouettes on paper and engravings in books—as well as a group of works by Thomas and other contemporary artists in a wide range of media. The book’s essays examine both how Thomas’s engagement with early American history opens up previously unexplored and fertile ground for her artistic practice and how this project constructs evocative spaces (both physically and textually) in which the lives of early nineteenth-century Black Americans can be recognized on their own terms. With an artist’s statement and extensive photography that captures details of the installation, this presentation documents an exciting direction for one of today’s most acclaimed artists.
Includes bibliographical references
Keywords: Thomas, Mickalene / 1971- / Exhibitions; Thomas, Mickalene -- 1971-; Geschichte 1800-1900; African American women / Portraits / Exhibitions; African American women in art / Exhibitions; Noires américaines - Portraits - Expositions; Noires américaines dans l'art - Expositions; exhibition catalogs; Exhibition catalogs; Catalogues d'exposition; Schwarze; Bildnis; Amerika; Ausstellungskatalog -- Yale University, Art Gallery -- 08.09.2023-07.01.2024 -- New Haven